The influence of earnings management on bank efficiency: the case of frontier markets. Issue 10 (October 2021) - Martens, Wil; Yapa, Prem; Safari, Maryam; Watts, Sean
Abstract: Frontier market banks fill key funding gaps in the markets they serve, resulting in increased evaluation (a positive) and earnings management (EM) (a negative). Examination of a large sample of banks in 22 frontier market countries from 2001 to 2018 reveals a downward trend in efficiency, indicating that loan quality issues persist despite increasing economic growth in the respective countries. Using stochastic frontier analysis to quantify efficiency and random effects and truncated regression to investigate the EM-efficiency relation, this study demonstrates that efficiency is negatively associated with EM. Furthermore, there was no clear relationship between bank size and efficiency, which counters economic efficiency theory and implies that frontier market banks absorb higher non-performing loan costs. The findings herein support prospect theory by demonstrating that managers engage in risk-seeking behaviour while making risk-averse decisions. Overall, the study's implications suggest that banks employ alternative loan provision practices to optimise resource allocation and, by extension, performance. Abstract : Stochastic frontier analysis; Earnings management; Frontier markets; Performance evaluation; Banking; Income smoothing